Relaxation behavior at high temperature associated with oxygen vacancy in the Sr1-x(LiCe)x/2.5Bi2Nb2O9 ceramics. (August 2023) - Pu, Songlin; Fang, Pinyang; Xu, Li; Guo, Feifei; Xi, Zengzhe
Highlights: Dielectric relaxation behavior and conductivity of Sr1-x (LiCe)x/2.5 Bi2 Nb2 O9 ceramics prepared by the solid-sate reaction method were investigated. Phase transition from normal ferroelectric to relaxor-like ferroelectric was detected in the Sr1-x (LiCe)x/2.5 Bi2 Nb2 O9 ceramics. Dielectric relaxation behavior at high temperature was attributed to the short-range conductivity of oxygen vacancies under thermal stimulation. Abstract: Dielectric relaxation behavior and conductiviy of Sr1- x (LiCe) x /2.5 Bi2 Nb2 O9 ceramics prepared by conventional solid-sate reaction method were investigated. With the introduction of the (LiCe), the conductivity was improved significantly and the large conductivity at high temperature (∼10 −4 S·cm −1 at 530 °C) could be obtained. Phase transition from normal ferroelectric to relaxor-like ferroelectric was detected in the Sr1- x (LiCe) x /2.5 Bi2 Nb2 O9 ceramics. Results of the complex impedance analysis indicated that the concentration of charge carriers increased gradually with the increase in (LiCe). Oxygen vacancy was confirmed to be responsible for the conductivity at high temperature by calculating activation energy of the carriers in the corresponding range of high temperature. Dielectric relaxation behavior at high temperature was attributed to the short-range conductivity of oxygen vacancies under thermal stimulation.